Awareness of Undergraduate Medical Students Regarding Child Sexual Abuse in Society - A Cross-Section Study - Rastogi, AK; Kumar, P; Gawali, D (Journal of Indian Academy of Forensic Medicine, 2024)
Child sexual abuse is a heinous crime of growing age children that may victimize both sexes of the child. Here, we tried to know the  concerns, opinions, and understanding related to the child sexual abuse of young undergraduate students of AIIMS Patna. These students  belonged to different communities, religions, and different states of India. Information was sent by mode using the google forms and was  collected automatically online. linkert-type questions were given to gather the information; collected data was analyzed and reported. 81.6  % of students disagreed that only girls are sexually abused and the rest, 18.4% of respondents were not sure about the given statement.  6.0% of respondents agreed that only girls are victims of sexual abuse. There, 225 (45.0 %) of students opined that child sexual abuse boys  are not homosexual, but the rest 226 (45.20) % of students, did not confirm the opinion. 100 (20%) students were neutral in opinion,  whereas 49 (9.80%) students opined with disagreement with the statement means indirectly, child sexually abused boys were homosexual.  Children from reputed families are not the victim of sexual abuse. 325 (65.0 %) of students disagree with the statement, 40 (8.0) % of  students opine that reputed family children are not sexually abused, 27% of students were not in the stage of any opinion or either neutral or  they do not know about the statement. 202 (40.4 %) of students opined that sexually abused children should not be sent to foster care, but 29  (5.8 %) of students disagreed with this opinion and suggested that they should be sent to foster care. 168 (53.60 %) participants had no  conclusive opinion and 23.4 % had a neutral opinion. Opinion of the participants regarding few children being victims of sexual abuse: 137  (27.4%) agree with that statement, a significant number of participants disagreed with this statement and opined that 223 (44.6%)  disagreed with the treatment, indirectly opined that a substantial number of children were the victim of child sexual abuse. The remaining  28 % of participants did not give a final opinion.
Keywords: Child sexual abuse (CSA); Indecent assault; Prostitution; Social taboos